PREVALENCE OF GASTROINTESTINAL HELMINTHS IN PASTORAL SHEEP AND GOAT FLOCKS IN THE CHOLISTAN DESERT OF PAKISTAN - M. A. Raza; M. Younas; E. Schlecht (Journal of Animal and Plant Sciences, 2014)
Small ruminants are a major source of cash for many rural populations, especially in semi-arid and arid regions of developing countries. Extensively managed animals often host gastrointestinal parasites, and even chronic infestations lead to economic losses. We evaluated the prevalence of gastrointestinal helminths in sheep and goats of the Cholistan desert, Pakistan, where livestock is the backbone of the regional economy. Fresh faeces (10 - 15 g) were collected from 500 sheep and 500 goats across five different localities. Standard parasitological techniques served to identify parasite eggs, and copro-culture enabled larval determination of specific nematodes. Overall helminth prevalence was 78.1% across the 1000 animals; pure nematode infestations were most prevalent (37.5%), followed by pure trematode (7.9%), pure cestode (2.6%) and pure protozoa infestations (0.8%). Mixed infestations with nematodes and trematodes occurred in 6.4% of all animals, mixed nematode-cestode infestations in 3.8%, and all three groups were found in 19.1% of the sheep and goats. In goats more males (81.1%) than females (77.0%) were infested, the opposite was found in sheep (73.6% males, 79.5% females). Parasites were especially prevalent in suckling goats (85.2%) and sheep (88.5%) and to a lesser extent in young (goats 80.6%, sheep 79.3%) and adult animals (goats 72.8%, sheep 73.8%). Given the high infestation rates, particular attention should be paid to management of suckling animals. A general means of reducing infestation rates might be the systematic testing of traditional plant-based remedies against helminths for cheap and regular deworming of the herds.
Keywords: Cestodes; Extensive grazing system; Gastrointestinal parasites; Small ruminants; Nematodes; Trematodes